Optimalisasi Rendemen Ikan Tuna (Thunnus Sp.) Loin Beku Dengan Metode Kaizen di PT. X-Jakarta Utara - Waluyo Waluyo; Aef Permadi; Randi B.S. Salampessy; Andi Perdana Gumilang; Diah Ayu Sri Utami; Niken Dharmayanti (Barakuda'45, 2022)
PT. X-North Jakarta produces Frozen Loin Tuna. The problem faced is the low value of yields that do not meet the company's standards. The purpose of the study is to (i) know the flow of the process of processing frozen loin tuna. (ii) understanding the quality of frozen loin tuna (iii) implementing kaizen using the fishbone method or a fish bone diagram (iv) understanding corrective actions for increasing yield and productivity (v) intervening in increasing yield and productivity (vi) calculating the estimated profit after interventionThe research was conducted from March to June 2021 at PT. X-North Jakarta. The method used is observation, with the type of data taken being primary and secondary data. Analysis of the Kaizen method obtained results showing that low yields were caused by several factors ranging from humans, methods, raw materials, and machines. After conducting an observation analysis of the yield value, it was found that the standard yield can be increased by 3% in tuna at a size of 20–50 kg, namely from the yield value of 49% can be increased to 52% and the size of 10–20 kg, the yield value of 48% can be increased to 51%. Profits can increase by Rp. 96,000/40 kg of raw materials with a 3% increase in size from 20 kg to 40 kg, and profits can increase by as much as Rp. 2,790,000,000/620,000 kg of raw materials if calculated over a time cycle (years). Improvements will occur if there is supervision and discipline of employees, equipment maintenance, and a need to carefully choose raw material.